Unravelling the Patterns of Suicidal Ideation and Attempts: Insights from Sociodemographic Factors, Triggers, and Psychiatric Comorbidities. - Rupa Lakshmi Harshavardhan; Pranay Krishna Penagaluru; Shehnaz Sultana (International Journal of Family Medicine and Public Health, 2025)
Background: Suicide is a significant public health issue, contributing to the global burden of the disease. According to the World Health Organization (WHO), one person dies by suicide every 40 seconds, with over 800,000 deaths annually. In India, suicide rates have reached an all-time high, with more than 100,000 deaths reported in 2021. Despite the increasing awareness and destigmatization efforts, suicidal ideation and attempts remain underreported, posing a significant challenge to the healthcare system. Objectives: This study aims to assess the sociodemographic, psychological, and clinical factors influencing suicidal ideation and attempts in individuals presenting to a tertiary care centre. Methods: A hospital-based cross-sectional study was conducted on individuals presenting with suicidal ideation or attempts. Data on sociodemographic characteristics, psychiatric comorbidities, psychosocial stressors, and personality traits were collected and analyzed. Standardized suicide risk assessment tools were used to classify the severity of ideation and the likelihood of transition to suicidal behavior. Results: Preliminary findings indicate a rising trend in suicide attempts, particularly among younger individuals, females, and those with psychiatric comorbidities such as depression, substance use disorders, and impulse control disorders. Sociodemographic determinants, stressful life events, and personality traits play a crucial role in suicide risk. Findings suggest that a significant proportion of individuals experiencing suicidal ideation transition to attempts within the first year of onset. Conclusion: Understanding the psychosocial and clinical determinants of suicidality is essential for targeted interventions and suicide prevention strategies. This study highlights the urgent need for comprehensive mental health screening, early intervention, and policy-driven approaches to suicide prevention in India. 1. Vijayakumar L, Chandra PS, Kumar MS, et al. The national suicide prevention strategy in India: context and considerations for urgent action. Lancet Psychiatry 2022;9(2):160-168. doi:10.1016/S2215- 0366(21)00152-8 2. World Health Organization. Suicide - India. Accessed April 22, 2025. https://www.who.int/india/health-topics/suicide 3. Bhatia G, Pal A, Sharma P, Parmar A. India’s National Suicide Prevention Strategy, 2022: A Critical Appraisal. Indian J Soc Psychiatry 2024;40(3):311-316. doi: 10.4103/ijsp.ijsp_97_23 4. Banandur P, Hasiruvalli Gangappa V, Koujageri JM, et al. Youth and suicidality: Correlates among clients attending youth mental health promotion clinics in India. Int J Soc Psychiatry 2022;69(1):146-155. doi:10.1177/00207640211070399 5. Krishnan M. Exploring Suicide Trends in India: An Analysis of Recent National Crime Records Bureau Data. Indian J Psychiatr Nurs 2023;20(2):179-180. doi: 10.4103/iopn.iopn_18_23 6. Government of India. The Mental Healthcare Act, 2017. Ministry of Law and Justice. Published April 7, 2017. Accessed April 22, 2025. https:// www.indiacode.nic.in/handle/123456789/2249 7. Sood P, Bindra S. Modified Kuppuswamy socioeconomic scale: 2022 update of India. Int J Community Med Public Health 2022;9(10):3841- 3844. doi:10.18203/2394-6040.ijcmph20222581 8. World Health Organization. The ICD-10 classification of mental and behavioural disorders: clinical descriptions and diagnostic guidelines. Geneva: World Health Organization; 1992. Accessed April 22, 2025. https://iris.who.int/handle/10665/37958 9. Loranger AW, Sartorius N, Andreoli A, et al. The International Personality Disorder Examination. The World Health Organization/Alcohol, Drug Abuse, and Mental Health Administration international pilot study of personality disorders. Arch Gen Psychiatry 1994;51(3):215-224. doi:10.1001/archpsyc.1994.03950030051005 10. Naina CM, Gupthan L, Michael JP. Socio-demographic factors and life events associated with high suicidal intent in youth with intentional self-harm: A cross-sectional study at a tertiary care centre in Kerala, India. Kerala J Psychiatry 2024;37(1):13-19. doi:10.30834/ KJP.37.1.2024.435 11. Selvaraj M, Sarkar S, Rajkumar RP. Suicidal ideation, suicide attempts and sexual harassment among transgender people in Puducherry, South India: a cross-sectional analytical study. Int J Community Med Public Health 2023;10(11):4126-4132. doi:10.18203/2394-6040. ijcmph20233157 12. van Ballegooijen W, Rawee J, Palantza C, et al. Suicidal ideation and suicide attempts after direct or indirect psychotherapy: A systematic review and meta-analysis. JAMA Psychiatry 2025;82(1):31-37. doi:10.1001/jamapsychiatry.2024.2854 13. Klonsky ED, May AM, Saffer BY. Suicide, suicide attempts, and suicidal ideation. Annu Rev Clin Psychol 2016; 12:307-330. doi:10.1146/ annurev-clinpsy-021815-093204 14. Brent DA, Melhem N. Familial transmission of suicidal behavior. Psychiatr Clin North Am 2008;31(2):157-177. doi: 10.1016/j. psc.2008.02.001 15. Muralidharan A, Peeples A, Lucksted A. Health behavior change processes among adults with serious mental illness engaged in illness self-management. Qual Health Res 2021;31(6):1155-1168. doi:10.1177/1049732321992049 16. Arya V, Page A, Vijayakumar L, et al. Changing profile of suicide methods in India: 2014-2021. J Affect Disord 2023; 340:420-426. doi: 10.1016/j.jad.2023.08.010 17. Vadlamani LN, Gowda M. Practical implications of Mental Healthcare Act 2017: Suicide and suicide attempt. Indian J Psychiatry 2019;61(Suppl 4): S750-S755. doi: 10.4103/psychiatry.IndianJPsychiatry_116_19